Higher serum selenium concentration is associated with lower risk of all-cause and cardiovascular mortality among individuals with chronic kidney disease: A population-based cohort study of NHANES - Zhu, Daiwen; Zhong, Qiang; Lin, Tao; Song, Turun (Frontiers in Nutrition, 2023)
Background Selenium is an essential nutrients and trace element required for human health and plays an important role in antioxidative and anti-inflammatory processes. However, the long-term impact of selenium levels on the health of patients with chronic kidney disease remains unclear. Method Participants in this study were 3063 CKD adults who come from the Third National Health and Nutrition Examination Survey (NHANES 1999–2000, 2003–2004, 2011–2018). The mortality status and cause of death of the study participants were obtained from the National Death Index records. For all-cause and cardiovascular disease (CVD) mortality, the models employed to estimate hazard ratios (HR) and 95% CI were Cox proportional hazards models and competing risk models respectively. Result During the follow-up period, 884 deaths occurred, including 336 heart disease-associated deaths. The median (IQR) concentration of serum selenium was 181.7 (156.1, 201.5) μg/L. After full adjustment, serum selenium levels were associated with a decreased risk of mortality in patients with CKD, including all-cause and CVD mortality (P<0.001). The multivariate-adjusted HRs (95%CI) were 0.684 (0.549–0.852) for all-cause mortality (P trend＜0.001) and 0.513 (0.356–0.739) for CVD mortality (P trend＜0.001) when selenium concentrations were compared according to the extreme quartiles. Selenium levels are inversely associated with an increased risk of all-cause mortality and CVD mortality. Similar results were observed in subgroup and sensitivity analyses. Conclusion Higher serum selenium concentration was independently associated with a decreased risk of all-cause and CVD mortality in patients with CKD.